Analisis Konfiksasi Bahasa Madura dalam Karya Sastra Cerpen pada Siswa SMP Muhammadiyah 1 Jember - Sila Rahmatina; Anindya Oktaviona Ervinawati; Adilah Puja Rahmawati; Hasan Suaedi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Language is a communication system used by a group of people to convey thoughts, feelings, and information. Language can be in the form of speech, writing, or sign, and has a structure consisting of vocabulary, grammar, and phonology. Each language has unique characteristics that reflect the culture and history of the user community. The means of communication used by humans to interact, which consists of a system of symbols and sounds that are arbitrary and meaningful. The purpose of this research is to analyze the confixation process in the Madura language contained in the short story "Tèra' È Konco'na Alas" by Miftahur, a student of SMP Muhammadiyah 1 Jember. Language as an important means of communication for social interaction, has various aspects that need to be researched, including morphology. In this context, the suffix affixation becomes the main focus, where this process involves the addition of suffixes at the beginning and end of the base word, which is a combination of prefixes and suffixes. The use of suffixes in the Madura language is an important aspect that reflects the richness of language morphology. Research results show that suffixes in the Madura language have significant variations, such as suffixes that function to form verbs, nouns, and adjectives. This research uses a qualitative descriptive approach, which emphasizes more on the presentation of meaning, description, and explanation of data in relevant contexts. In the use of suffix in making short stories in Madura language.